2005
DOI: 10.4049/jimmunol.175.7.4189
|View full text |Cite
|
Sign up to set email alerts
|

Cutting Edge: TLR2-Mediated Proinflammatory Cytokine and Chemokine Production by Microglial Cells in Response to Herpes Simplex Virus

Abstract: Recent studies indicate that TLRs are critical in generating innate immune responses during infection with HSV-1. In this study, we investigated the role of TLR2 signaling in regulating the production of neuroimmune mediators by examining cytokine and chemokine expression using primary microglial cells obtained from TLR2−/− as well as wild-type mice. Data presented here demonstrate that TLR2 signaling is required for the production of proinflammatory cytokines and chemokines: TNF-α, IL-1β, IL-6, IL-12, CCL7, C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
175
0
1

Year Published

2007
2007
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 214 publications
(185 citation statements)
references
References 25 publications
9
175
0
1
Order By: Relevance
“…Since mice lacking 1 2 3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 58 59 60 61 62 63 64 65 28 TLR2 exhibit reduced mortality and neuroinflammation from brain infection by HSV-1, it is suggested that TLR2 can mediate the pathogenesis of this viral infection [93,94]. It has also been found that TLR2 mediates apoptosis in microglia in response to HSV infection [95].…”
Section: Tlrs and Herpes Simplex Encephalitismentioning
confidence: 99%
“…Since mice lacking 1 2 3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 58 59 60 61 62 63 64 65 28 TLR2 exhibit reduced mortality and neuroinflammation from brain infection by HSV-1, it is suggested that TLR2 can mediate the pathogenesis of this viral infection [93,94]. It has also been found that TLR2 mediates apoptosis in microglia in response to HSV infection [95].…”
Section: Tlrs and Herpes Simplex Encephalitismentioning
confidence: 99%
“…Analysis of the TLR system in the pathogenesis of HSV infection further supports the notion that TLR interactions catalyze virus-induced inflammation. A number of recent studies have demonstrated that TLRs expressed by peritoneal macrophages and microglial cells, which are key immune cells that survey the brain parenchyma, are pivotal in identifying and generating the first line of innate immune responses against viral pathogens in the central nervous system , 2005Olson and Miller, 2004;Aravalli et al, 2005;Town et al, 2006). Although specific viral ligands for TLR2 have not been identified (Sato et al, 2006), which may have major roles in virus entry and initiate innate immune recognition at this early stage of the viral life cycle, recent studies suggest that TLR2 signaling may be involved in innate responses to HSV.…”
Section: Hsv and Tlr2mentioning
confidence: 99%
“…In vitro, most studies show that HSV-induced expression of proinflammatory cytokines and chemokines, such as TNF-α, IL-1, IL-6, IL-12, CCL7, CCL8, CCL9, CXCL1, CXCL2, CXCL4 and CXCL5, as well as the focal tissue damage (if left untreated, can result in prolonged brain inflammation and compromised brain function or death) (Aravalli et al, 2005;Marques et al, 2006Marques et al, , 2008aMarques et al, , 2008bArmien et al, 2010), is diminished when TLR2 is not functional (Aravalli et al, 2005). In a recent report, Boivin and colleagues (Boivin et al, 2002) described the enhanced expression of TLR2 in the hindbrain of mice infected with HSV-2.…”
Section: Hsv and Tlr2mentioning
confidence: 99%
“…In this regard, it has been reported that fragments of gD can induce an IFN-α response, implying that gD could interact with TLRs [308]. It has been found that glycoprotein-dependent and TLR2-indipendent innate immune recognition evokes a set of proinflammatory cytokines such as: TNF-α, IL-1( [309]. TLR2 recognition may be particularly important during HSV-1 encephalitis, as microglia strongly express TLR2 [309, 310].…”
Section: Factors That May Affect Hsv Vectors Efficacymentioning
confidence: 99%
“…It has been found that glycoprotein-dependent and TLR2-indipendent innate immune recognition evokes a set of proinflammatory cytokines such as: TNF-α, IL-1( [309]. TLR2 recognition may be particularly important during HSV-1 encephalitis, as microglia strongly express TLR2 [309, 310]. Recently, it has been shown that the complex of the four glycoproteins gB, gD, gH and gL, which are essential for viral attachment/entry (Fig.…”
Section: Factors That May Affect Hsv Vectors Efficacymentioning
confidence: 99%